Prevalence of suicidal behaviour among nursing and midwifery college students in Ghana. Issue 3 (9th April 2019) - Quarshie, Emmanuel Nii‐Boye; Cheataa‐Plange, Haziel Vera; Annor, Francis; Asare‐Doku, Winifred; Lartey, Joshua King Safo
Abstract: Aim: To provide exploratory and descriptive evidence on the prevalence estimate and some demographic correlates of suicidal behaviour among nursing and midwifery college students in Ghana. Design: We used a cross‐sectional survey design. Method: An anonymous survey involving a randomly selected sample of 305 nursing and midwifery college students was conducted in March–May 2017. The Suicide Behavior Questionnaire‐Revised was used to assess suicidal behaviour (i.e., ideation, planning, threat and attempt) and suicidal behaviour risk. Results: The lifetime prevalence of suicide ideations (15.4%; 95% confidence interval [CI] = 0.11–0.20), plans (6.6%; 95% CI = 0.04–0.10), attempts (2.3%; 95% CI = 0.01–0.05), threats (13.4%; 95% CI = 0.10–0.18) and 12‐month prevalence of ideations (21.3%; 95% CI = 0.17–0.26) are comparable to estimates found in both high‐income and low‐ and middle‐income countries. However, associations between the demographic variables studied and suicidal behaviour risk were not statistically significant.